THE USE OF THE INFUSION DRUG BASED ON SORBITOL IN ONCOLOGICAL PATIENTS AFTER RESECTION OF THE SIGMIOID BOWEL IN THE EARLY POSTOPERATIVE PERIOD - Novak, Василь; Dzis, Богдан; Varyvoda, Євген; Kryvko, Юрій; Dzis, Роман; Kondratsky, Богдан; Varyvoda, Василь; Stasyshyn, Олександра; Tarasiuk, Олександра; Krasivska, Валерія; Karpovych, Євгенія; Chaban, Володимир (Actual Problems of Medicine and Pharmacy, 2023)
According to the World Health Organization, there is an increase in the incidence of cancer. Experts emphasize the need for decisive action and joint efforts between countries in the fight against cancer. The search for modern, effective, safe, and economically available drugs for the pharmacotherapy of cancer patients is a task of the health care sector. Clinical studies of the complex infusion drug "Sorbilact" carried out by the authors indicate that the complex drug "Sorbilact" is a solution of multifunctional action, exhibits a detoxifying and energetic effect. Infusion therapy has a positive clinical effect, which is expressed in the restoration of peristalsis of the gastrointestinal tract on the 2nd day after surgery. Wounds heal more quickly with primary tension. Functional insufficiency of intestinal anastomosis does not develop in operated patients. Further studies of the drug are relevant at the level of pharmacoeconomic availability for different contingents of patients.